The Economic Stakes of Biodiversity Loss in Africa and Measures Implemented to Limit It - (:unkn) unknown (My University, 2024)
While African countries have a particularly rich biodiversity, this has been deteriorating markedly for several decades, and seems to be accelerating in recent years. This degradation of biodiversity has consequences both at local level—African populations, mostly rural, are heavily dependent on ecosystem services—and at global level, given the major implications of biodiversity degradation for global warming, health, food security and global financial stability. Biodiversity conservation in Africa is therefore a major challenge, and its linkage with the continent’s economic development objectives raises a number of issues. This article studies the impact of economic activity on biodiversity. Using geolocated databases from 1990 to 2015, it shows that an increase in local economic activity is associated with a decline in local vertebrate populations. The article also discusses the protection measures implemented both locally and globally to promote biodiversity preservation, as well as the challenges they face.
Keywords: African Research